An offer you can't refuse – Enhancing personal productivity through 'efficiency consumption' - Andreas Siemoneit (ZOE. Institut für zukunftsfähige Ökonomien, 2019)
Worldwide, economic growth is a prominent political goal, despite its severe conflicts with ecological sustainability. Contributing to the debate on economic 'growth imperatives', this article explores the thesis that firms and consumers both frequently acquire goods that increase their efficiency (productivity). For firms, efficiency is accepted as a main investment motive, but for consumers it is usually framed as convenience, ease, or comfort. Via social diffusion processes consumption goods that can save time and costs are transformed from a welcome expansion of possibilities into a social imperative whose noncompliance over time also has economic drawbacks. Positive feedback mechanisms not only lead to an acceleration of private life but favor ever more efficient industry and trade structures on the supply side, contributing to a redistribution of incomes and revenues. Eventually a comprehensive consumption pattern leads to a new 'normality' and makes the renunciation of consumption goods like cars, computers or smartphones literally impossible. Both microeconomics and consumption sociology usually assume fundamental differences of motivations, goals and structural overall conditions for firms and consumers. Some reasons for this scholarly asymmetry are discussed and a more symmetrical consumption model is proposed. As a political dimension the increasing resource use of this quest for efficiency is addressed.
Keywords: 330; Efficiency; Diffusion of Innovations; Growth Imperative; Feedback loops; Theory of Consumption